Occupational injury burden among gold miners in Ghana. Issue 4 (2nd October 2019) - Nakua, Emmanuel Kweku; Owusu-Dabo, Ellis; Newton, Samuel; Adofo, Koranteng; Otupiri, Easmon; Donkor, Peter; Mock, Charles
Abstract: The mining environment is particularly dangerous in low- and middle-income countries. We sought to better understand the burden, characteristics and risk factors associated with gold mining, through a household survey of 1, 029 miners in four districts, in Ghana. We found a high burden of injuries, with 25.5% of workers injured in the past year, giving an incidence of 19.67 injuries per 200, 000 hours worked. Notably, an increase in injury risk was associated with work in the informal mining sector ( galamsey ), with an adjusted injury incidence ratio of 1.57 (95%CI: 1.12, 2.19) compared with miners in the formal sector. Half of gold miners in Ghana work in galamasey, and this sector is a high priority for safety promotion. Improving the safety of the equipment, which accounted for nearly half (46.2%) of galamsey -related injuries, could be a prime target for improving safety.